Euconnus (Rhomboconnus): redescriptions of species described by Schaufuss and Sharp, and descriptions of five new Mexican species (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2020)
To date, the subgenus Rhomboconnus Franz of Euconnus Thomson was represented by twelve species known to occur in Bolivia, Ecuador, Panama, Peru, and Venezuela. Examination of Neotropical species described by David Sharp and Ludwig Wilhelm Schaufuss revealed that two more species, previously not recognized as members of Rhomboconnus, occur in Guatemala and Brazil: Euconnus cavifrons (L.W. Schaufuss) and E. giraffa Sharp. The latter species was redescribed by Herbert Franz and recorded to occur in Mexico. Franz’s ‘redescription’, however, was based on misidentified specimens. Five new species are described, all known to occur in souther n Mexico: Euconnus (Rhomboconnus) agiraffa sp. n., Euconnus (Rhomboconnus) oaxacanus sp. n., Euconnus (Rhomboconnus) bicarinatus sp. n., Euconnus (Rhomboconnus) cordobanus sp. n., and Euconnus (Rhomboconnus) maya sp. n.